El incumplimiento de la reinserción social de las personas que han sido sentenciadas con pena privativa de la libertad - Alvarado Guerrero, María José (2016)
The present titled thesis work; "The nonfulfillment of the social reinserción of people that you/they have been sentenced with exclusive pain of the freedom", it is of great relevance and social transcendencies, because we should have present that the new tendency of the modern penal right points to application to the integral rehabilitation of the one sentenced, with the purpose that is reinserted in the society so that he/she has a new opportunity to adapt its behavior to the legal norms of the judicial régime and culture of the Ecuadorian society. Therefore, it is the executive's obligation to look after the faithful execution of the rights of the interns that you/they are completing a pain to alter the public order and to injure the other people's right protected as very juridical by the State. Whichever it is the made crime the offender should receive treatment that influences in his integral social rehabilitation. When investigating this topic, collapsed encounter the penitentiary system of our country, being significant the state economic expense for the maintenance of the prisoners; where in fact social rehabilitation doesn't exist. The theoretical work and of field of the present thesis it allowed me to obtain approaches, with clear and precise foundations, of very grateful bibliography that you/they contributed to the verification of objectives, and contrastación of the outlined hypotheses, allowing to support the proposed changes. The content of the thesis is the author's intellectual effort in the scientific and methodological environment that approaches theoretical and empirically, the limitation to the fundamental right of the individual rehabilitation, and in view of the ability that it grants the Code of Execution of Hardships and Social Rehabilitation to the Judges of Penitentiary Guarantees in to complete and to make complete the integral rehabilitation of the interns that you/they are private of its freedom in the prison Centers of the Ecuador, without receiving appropriate and opportune interdisciplinary attention so that they achieve its social reinserción.